Helmintofauna gastrointestinal de Cuniculus paca (Linnaeus 1766) “majaz” de vida silvestre procedentes de las cuencas de los ríos Pucacuro y Yavarí-Mirin, Loreto - Aching Gonzales, Alexis Jesús (2024)
The study was conducted in order to determine the gastrointestinal helminth fauna of wild Cuniculus paca from the Pucacuro and Yavarí-Mirin river basins. The sample consisted of the gastrointestinal contents of 60 specimens of C. paca. The analysis of the samples was carried out using the direct method and sedimentation in a tube. The search for adult worms was carried out by direct observation with a stereoscope. Nine gastrointestinal helminths were identified: Vianella, Eucyathostomum, Strongyloides, Boehmiella, Trichuris, Physaloptera, Trichostrongylus, Ascaris and Stichorchis; which are grouped into 6 orders and 8 families. The highest average abundance was found in the Trichuris genus with an average of 1 specimen per sample. Likewise, the prevalence indicates that Trichuris was the most prevalent in both basins (in Pucacuro with 52% and in Yavarí Mirin 34.3%). The similarity of C. paca helminths was high in the Pucacuro and Yavarí-Mirin river basins, with 71.42%. Trichuris, Strongyloides, Trichostrongylus and Ascaris were also identified as gastrointestinal helminths of zoonotic interest present in the C. paca samples. In conclusion, the results of this research demonstrate that gastrointestinal helminths are present in rodents such as Cuniculus paca, and their richness, abundance and prevalence are related to the habitat conditions and habits of the species that are important for the favorable development of the parasites.